The Urgency of the Need for Energy Transition in Africa: A Case Study of Ghana - Eduah, Dominic Kwesi (Advances in Social Sciences Research Journal, 2025)
Africa faces a critical energy challenge characterized by a heavy reliance on fossil fuels, limited electricity access — especially in rural areas - and underinvestment in renewable energy infrastructure. This paper examines the urgency of the energy transition across the continent, using Ghana as a case study. While nations such as Kenya and Ethiopia have advanced in their use of renewable energy, Ghana still relies heavily on fossil fuels due to challenges in infrastructure, national programs, and financing. Around 80% of the population in Ghana has access to electricity, but the disparity in the access of electricity between urban and rural areas remains an outstanding issue. This study paper calls attention to how the reliance on fossil fuels not only impacts energy security but also leads to Ghana’s economic instability and environmental harm. The research paper suggests an actionable swift shift towards sustainable energy through heightened investments in renewable sources, the establishment of more robust policy frameworks, and enhanced energy efficiency to properly address this issue. For Ghana, effective strategies include broadening renewable energy capabilities, updating infrastructure, promoting private sector participation, and implementing regulatory reforms that offer support. A successful transition would foster inclusive economic development across Africa in addition to ensuring cleaner, more reliable energy.